2011
DOI: 10.1055/s-0030-1250590
|View full text |Cite
|
Sign up to set email alerts
|

Vergleich von minimalinvasivem und transglutealem Zugang zur Implantation von Hüfttotalendoprothesen. Klinik und Ganganalyse

Abstract: Advantages of minimally invasive approaches in total hip replacement which can be found a short time after surgery (like less blood loss, less pain after operation, quicker beginning of mobilisation) were not found in this study 5 weeks later regarding functional outcomes. Persistence of functional deficits, caused by damage to the arthromuscular complex, which occur during the process of the development of the arthrosis, need much more time to recover after surgery, independent of the used approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…Hip RoM in the sagittal plane was reduced in almost all studies compared to healthy controls (Beaulieu et al, 2010;Bennett et al, 2008;Foucher et al, 2007;Kiss and Illyes, 2012;Madsen et al, 2004;Perron et al, 2000;Varin et al, 2013) as well as compared to the nonoperated limb (Benedetti et al, 2010;Kiss and Illyes, 2012). Peak hip extension was consistently reduced compared to controls (Beaulieu et al, 2010;Bennett et al, 2008;Perron et al, 2000;Sander et al, 2011;Tanaka, 1998;Varin et al, 2013). Peak hip flexion was most often similar to controls (Bennett et al, 2008;Kiss and Illyes, 2012;Tanaka, 1998;Tateuchi et al, 2011), but was reduced in some studies (Beaulieu et al, 2010;Kiss and Illyes, 2012 (anterolateral group)).…”
Section: Kinematicsmentioning
confidence: 86%
“…Hip RoM in the sagittal plane was reduced in almost all studies compared to healthy controls (Beaulieu et al, 2010;Bennett et al, 2008;Foucher et al, 2007;Kiss and Illyes, 2012;Madsen et al, 2004;Perron et al, 2000;Varin et al, 2013) as well as compared to the nonoperated limb (Benedetti et al, 2010;Kiss and Illyes, 2012). Peak hip extension was consistently reduced compared to controls (Beaulieu et al, 2010;Bennett et al, 2008;Perron et al, 2000;Sander et al, 2011;Tanaka, 1998;Varin et al, 2013). Peak hip flexion was most often similar to controls (Bennett et al, 2008;Kiss and Illyes, 2012;Tanaka, 1998;Tateuchi et al, 2011), but was reduced in some studies (Beaulieu et al, 2010;Kiss and Illyes, 2012 (anterolateral group)).…”
Section: Kinematicsmentioning
confidence: 86%
“…In einer prospektiven Studie [29] sollten die kurz-und mittelfristigen Operationsergebnisse von Patienten mit primä-rer Koxarthrose nach Einsatz eines anterolateralen, minimal-invasiven und eines konventionellen, transglutäalen Zugangs vergleichend untersucht werden. Zusätz-lich zur Ganganalyse wurden klinische Untersuchungen durchgeführt und der orthopädische Status der Patienten (subjektiv) bewertet.…”
Section: Minimal-invasiver Vs Konventioneller Zugangunclassified
“…In addition, the results disagree with Sarzaeim, Darestani, Kazemian, Amuzadeh and Feizi (2015) who indicated that the average standard of Harris scale was good (79.8) six months after the surgery, and a year later it was excellent (91.2) [57] . This result also is inconsistent with Edmunds and Boscainos (2011) and Sander, Layher, Babisch, and Roth (2011) each have separately reported the increase in Harris scale and the improved performance of THR surgery [58,59] .…”
Section: Discussionmentioning
confidence: 74%